The Impact of Human Behavior on Dolphin’s Life in the Dolphin Tale Series (2011 & 2014) - Kuni Maskurotal Azizah; Mimien Aminah Sudja’ie; Rizki Februansyah (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2020)
This research aims to figure out how human’s behaviors affect the dolphin’s life in Dolphin Tale. The researcher used qualitative method to analyze the data. The primary data are taken from Charles Martin Smith’s movies entitled Dolphin Tale (2011) and Dolphin Tale 2 (2014). In addition, the researcher used ecocriticism approach to analyze the positive and negative impacts of the human’s behavior on the dolphin’s life. Theories of human and nature and dolphin studies are also used to analyze the impacts of the human’s behavior on the dolphin’s life. The results show that some human behaviors can give negative impacts while some other give positive impacts to the dolphin’s life. The negative impacts can be seen on the dolphin that gets injured because of human behavior. Meanwhile, the positive ones can be seen on the dolphin that is successfuly recovered. Based on those findings, it can be concluded that there should be a balance of human behaviors which affect the dolphin’s life.